Great-Circle Migration Of Arctic Passerines - Alerstam, Thomas; Bäckman, Johan; Strandberg, Roine; Gudmundsson, Gudmundur A.; Hedenström, Anders; Henningsson, Sara; Karlsson, Håkan; Rosén, Mikael (The Auk, 2008)
Birds can save distance and time on their migratory journeys by following great circles rather than rhumblines, but great-circle routes require more complex orientation with changing courses. Flight directions at different places along the route and in relation to the destination can be used to test whether birds migrate along great circles or rhumblines. Such data have indicated great-circle migration among shorebirds at high latitudes, but no critical tests have been made for passerines. Using tracking radar on board the icebreaker Oden in August 2005, we recorded westerly flight directions of passerine migrants over the Chukchi Sea. The main sector of migratory directions was 237-311 degrees centered oil a mean heading direction of 274 degrees. The most likely species to participate in this westward trans-Beringia migration, mainly departing from Alaska, were Eastern Yellow Wagtail (Motacilla Ischutschensis), Arctic Warbler (Phylloscopus borealis kennicotti), Northern Wheatear (Oenanthe oenanthe), and Bluethroat (Luscinia svecica); all except the Bluethroat were recorded from the ship. Observed flight directions agreed with predicted great-circle courses but not with rhumbline courses for three of these four species with winter quarters in Southeast Asia; no definite conclusion could be drawn for the Northern Wheatear (wintering in East Africa). These results support great-circle migration among passerines traveling between Alaska and Old World winter quarters, though the long-distance precision and orientation mechanisms are Still unknown. The relative importance of different evolutionary causes-such as circumvention of geographic barriers, retracing of ancient colonization ways, or distance reduction by great-circle migration-to complex bird migration routes with changing courses remains to be understood. Received 24 August 2007, accepted 6 March 2008.